Neighborhood Socioeconomic Disadvantage and 30‐Day Outcomes for Common Cardiovascular Conditions - Jay B. Lusk; Beau Blass; Hannah Mahoney; Molly N. Hoffman; Amy G. Clark; Jonathan Bae; Robert J. Mentz; Tracy Y. Wang; Manesh Patel; Bradley G. Hammill (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Understanding the relationship between neighborhood environment and cardiovascular outcomes is important to achieve health equity and implement effective quality strategies. We conducted a population‐based cohort study to determine the association of neighborhood socioeconomic deprivation and 30‐day mortality and readmission rate for patients admitted with common cardiovascular conditions. Methods and Results We examined claims data from fee‐for‐service Medicare beneficiaries aged ≥65 years between 2017 and 2019 admitted for heart failure, valvular heart disease, ischemic heart disease, or cardiac arrhythmias. The primary exposure was the Area Deprivation Index; outcomes were 30‐day all‐cause death and unplanned readmission. More than 2 million admissions were included. After sequential adjustment for patient characteristics (demographics, dual eligibility, comorbidities), area health care resources (primary care clinicians, specialists, and hospital beds per capita), and admitting hospital characteristics (ownership, size, teaching status), there was a dose‐dependent association between neighborhood socioeconomic deprivation and 30‐day mortality rate for all conditions. In the fully adjusted model for death, estimated effect sizes of residence in the most disadvantaged versus least disadvantaged neighborhoods ranged from adjusted odds ratio 1.29 (95% CI, 1.22–1.36) for the heart failure group to adjusted odds ratio 1.63 (95% CI, 1.36–1.95) for the valvular heart disease group. Neighborhood deprivation was associated with increased adjusted 30‐day readmission rates, with estimated effect sizes from adjusted odds ratio 1.09 (95% CI, 1.05–1.14) for heart failure to adjusted odds ratio 1.19 (95% CI, 1.13–1.26) for arrhythmia. Conclusions Neighborhood socioeconomic disadvantage was associated with 30‐day mortality rate and readmission for patients admitted with common cardiovascular conditions independent of individual demographics, socioeconomic status, medical risk, care access, or admitting hospital characteristics.